E-Sungai Dulang: The development of website for embracing community empowerment and leadership in digital environment - Talip, Bakhreza; Muhammad Anas Syazwi Warman,; Muhamad Daniel Emir Nazaruddin,; Wan Amirul Hakim Wan Kamarulfarid, (Multidisciplinary Applied Research and Innovation, 2022)
The development of the E-Sungai Dulang website motivated by the government initiative in urbanizing rural regions through digitization. The community leader (Ketua Kampung) and the residents (Penduduk Kampung) are expected to have digital abilities that not only limited on the smartphone but also with other digital equipment that includes laptop, printer and the internet. A website will be a significance platfom for rural communities empowering themselves to adapt with on the web communication platform which not always have direct and linear interaction as provided in mobile messenger apps. There is a need to embark on this project as from the interview conducted, none community leader has used website as part of their administrative work for the village and with the villagers.